The Influence Of Leadership Style And Interpersonal Communication On Work Effectiveness With Job Satisfaction As Mediation Variables - Fajar Taufik Putranto; Dewi Susita; Agung Wahyu Handaru (Journal of Business and Management Review, 2022)
This study aims to analyze the effect of leadership style and interpersonal communication on work effectiveness with job satisfaction as a mediating variable. The population in this study are subjects related to the research that the author did at PT Reasuransi Nasional Indonesia. The sample size uses indicator calculations multiplied by 5 so that 205 respondents are obtained. The analytical method used in this research is Structural Equation Modeling based on Partial Least Square (PLS). The results showed that there was a significant positive effect between leadership style on work effectiveness, interpersonal communication had a significant positive effect on work effectiveness, leadership style had a significant positive effect on job satisfaction, interpersonal communication had a significant positive effect on job satisfaction, job satisfaction had a significant positive effect on work effectiveness. , leadership style has an indirect effect on work effectiveness through job satisfaction, interpersonal communication has an indirect effect on work effectiveness through job satisfaction